2022
DOI: 10.3390/polym14193978
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of Polybutylene Succinate Biodegradation by Terribacillus sp. JY49 Isolated from a Marine Environment

Abstract: Polybutylene succinate (PBS) is a bioplastic substitute for synthetic plastics that are made from petroleum-based products such as polyethylene and polypropylene. However, the biodegradation rate of PBS is still low and similar to that of polylactic acid (PLA). Moreover, our knowledge about degrader species is limited to a few fungi and mixed consortia. Here, to identify a bacterial degrader to accelerate PBS degradation, we screened and isolated Terribacillus sp. JY49, which showed significant degradability. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…Such a feature against NaCl is unexpected in a secreted enzyme originating from marine bacteria. Accumulated knowledge from discoveries of bacteria from marine environments (Lee et al, 2013; Kim et al, 2022) including Vr19890 suggested that PBS and PBSA can be degraded under marine conditions. Current biodegradability evaluation methods consider only the enzymes that biodegrade in a relatively short period as being able to biodegrade.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such a feature against NaCl is unexpected in a secreted enzyme originating from marine bacteria. Accumulated knowledge from discoveries of bacteria from marine environments (Lee et al, 2013; Kim et al, 2022) including Vr19890 suggested that PBS and PBSA can be degraded under marine conditions. Current biodegradability evaluation methods consider only the enzymes that biodegrade in a relatively short period as being able to biodegrade.…”
Section: Discussionmentioning
confidence: 99%
“…The growth of Terribacillus sp. JY49, a PBS‐degrading bacterium, was inhibited by the presence of high concentrations (>8 mM) of succinate, the monomer component of PBS, which prolonged the time to increase the degradation yield of the PBS film (Kim et al, 2022). In V. ruber , PBSase was not affected by end products.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Terribacillus sp. JY49 was isolated from marine samples and exhibited degradability to PBS [ 22 ]. Bacillus sp.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have focused on the degradation of PBS, a material commonly used in everyday applications, due to the action of individual bacterial strains. However, research on PBS degradation by consortia comprising multiple bacterial strains is scarce ( Table 1 ) [ 20 , 21 , 22 , 23 , 24 , 25 ]. Various species of Bacillus and Terribacillus , isolated from environmental sources, are known for their ability to degrade different types of polyester plastics.…”
Section: Introductionmentioning
confidence: 99%